EFFECTIVENESS COMPARATIVE OF SCIENTIFIC APPROACH ELPSA AND OPEN-ENDED SETTING COOPERATIVE STAD TYPES OF MATHEMATICS LEARNING AT VII CLASS SMP NEGERI OF A ACCREDITATION IN MAKASSAR - Andi Kaharuddin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
Thisstudyaimedto:(1)describetheeffectiveness oftheScientificlearningapproachsetting cooperativeSTADTypesinmathematicslearningatstudentsofclassVIISMPNegeriof A-AccreditationinMakassar;(2)   describetheeffectivenessofELPSA learningapproach settingcooperativeSTADtypeinmathematicslearningatstudents ofclassVIISMPNegeriof A-Accreditation inMakassar;(3)describetheeffectivenessofOpen-Endedlearningapproach settingcooperativeSTADtypeinmathematicslearningatstudents ofclassVIISMPNegeriof A-Accreditation inMakassar;(4)describecomparativeeffectivenessofScientificlearning approach,ELPSAandOpen-EndedSettingCooperativeSTADTypesofMathematicsLearning atStudentsofclassVIISMPNegeriofA-Accreditation inMakassar.Thepopulationinthis researchwereallofstudentsatclassVIISMPNegeriofA-AccreditationinMakassarandthe sampleconsistedthatselectedbyusingaclusterstratifiedrandomsamplingtechnique. The resultofttestonthelevelofsignificantα=0.025atthemajorhypothesis (1)the implementation oftheScientificapproachiseffective(2)theimplementation oftheELPSA approachiseffective, (3)theimplementationoftheOpen-Endedapproachiseffective, andthe resultof anovatest on thelevelof significantα=0.05atthemajor(4)to (a)learningoutcomes (posttest,gain)(b)interestinlearning(c)response,theresultofequalitytwoproportions test there  is  no  differences  implementation  in  Scientific  approach  application,  ELPSA  and Open-EndedSettingCooperativeSTAD TypesinmathematicslearningatstudentsofclassVII SMPNegeriofA-AccreditationinMakassar